Escucho la narración de un cuento la gallina colorada - Quispe Benites, Kely (2019)
The purpose of this sufficiency work is to promote meaningful learning regarding oral communication through short stories in students of the second grade of primary education._x000D_ The learning session corresponds to the area of communication and was developed following the recommendations of the communicative approach that has been proposed by the Ministry of Education, as well as the pedagogical and didactic processes necessary for the achievement competition learning is communicated orally in their native language._x000D_ Teaching and learning strategies were used to promote active and meaningful participation of all students._x000D_ The learning session will be evaluated through a checklist to assess performance achievement.